Surgery of the autonomic nervous system - Hyam, Jonathan A.; Pereira, Erlick A. C.; Green, Alexander L. (Oxford University Press, 2016)
This book reviews the basic science underpinning the autonomic control of various body systems as well as the state-of-the-art clinical applications by which these systems are surgically modulated in patients today.